Multifunctional bismuth ferrite nanomaterials as a new-generation catalyst for water treatment - Hu, Zhong Ting (2017)
Tons of recalcitrant pollutants are entering into the natural water cycle from industrial manufacturers, agricultural irrigations, households and landfills. Conventional technologies for water treatment cannot efficiently remove many of the recalcitrant pollutants. Solar energy is considered as one of the most promising renewable energy. As such, a green water technology that shows removal of recalcitrant pollutants utilizing solar light is much desirable. The aims of this study were to develop a range of novel nanostructured bismuth ferrite (BFO) catalysts, and investigate their performances in removal of recalcitrant pollutants in water. The as-prepared BFO could be in the forms of nanoparticle, single crystal, cluster, hierarchical nanostructure, 2D composite, and 3D multi-phase composite via facile or delicate synthesis methods. The multi-functionalized BFOs exhibited multiplex heterogeneous catalyses at circumneutral pH, including photocatalysis, photo-Fenton and Fenton-like (in dark) oxidations, for effective degradation of different types of organic pollutants (e.g., dyes, pesticides and pharmaceuticals) under visible light of the simulated solar spectrum. The BFO post-treated by a solvothermal method also could be used to remove different types of heavy metal ions via physical adsorption and could be recovered easily via magnetic separation. The mechanism of formation of reactive oxygen species through BFO-driven catalyses was investigated and defined as hybrid advanced oxidation processes (HAOPs).